Seminal Plasma Bisphenol A Concentrations Among Men with Secondary and Primary Infertility (Journal of Basic and Applied Research in Biomedicine, 2023)
Background: The declining trend of male infertility have been attributed to some factors including environmental, lifestyle behaviors, and dietary habits. Bisphenol A (BPA) which is preponderance in the environment and in various products frequently used has been implicated in male infertility. It is not known whether the seminal fluid BPA concentrations differ among men with primary infertility and secondary infertility. This study was aimed at determining the seminal plasma BPA concentrations among men with secondary infertility and primary infertility and to associated their levels with duration of infertility. Materials and Methods: This was a cross‑sectional study of 145 men clinically diagnosed with primary infertility (n=80) and secondary infertility (n=65), and men with proven fertility (n=60) as controls. Semen analysis was done manually according World Health Organization guidelines and seminal plasma BPA was assayed using an Elisa kit. Chi square and Student’s t-test were used to analyze continuous data and discrete variables respectively. Pearson’s correlation coefficient was used to determine the association between seminal plasma BPA and duration of infertility, and a p